Enhancement of bioelectricity and hydrogen production from xylose by a nanofiber polyaniline modified anode with yeast microbial fuel cell. (15th October 2022) - Moradian, Jamile Mohammadi; Yang, Fu-Qiao; Xu, Nuo; Wang, Jia-Yi; Wang, Jing-Xian; Sha, Chong; Ali, Amjad; Yong, Yang-Chun
Graphical abstract: Highlights: The Polyaniline (PANI) was synthesized under ionic liquid at room temperature. PANI modified anode increased accumulation of exoelectrogens yeast JSUX1. MFCs with PANI/CF improved the production of biohydrogen and electricity from xylose. PANI accelerated extracellular electron transfer between yeast cells and electrodes. Abstract: In this study, modification of carbon felt (CF) electrode using polymerized nanofiber polyaniline (PANI) was developed for increasing the conductivity of anodic electrode toward efficient adherence of exoelectrogenic yeast cells of Cystobasidium slooffiae JSUX1 and further enhancing both bioelectricity and hydrogen production from xylose in MFCs. The morphology analysis with SEM images verified the formed nanofiber structure of PANI on the surface of the PANI/CF electrode. Nanofiber PANI with a higher surface area could improve the conductivity of the PANI/CF anode for a durable attachment of yeast C. slooffiae JSUX1 to form a dense biofilm and boost a high-performance in MFCs. The maximum derived power output of MFCs with PANI/CF (119.35 ± 3.27 mW/m 2 ) was about 2.2 times higher than that of MFCs with the bare CF (50.41 ± 6.9 mW/m 2 ) and the maximum hydrogen yield reached 25.83 mL by using xylose as the sole carbon source. The obtained results of PANI/CF modified electrodes compared to the bare CF anode suggested that the extracellular electron transfer (EET) and energy production by yeast cell C. slooffiae JSUX1 have an excellent capability to be improved by PANI polymers in MFCs.